Production and Reproductive Performance of Bhadawari Buffaloes in Uttar Pradesh, India - Kushwaha, B.P.; Singh, Sultan; Das, N.; Maity, S.B.; Singh, K.K.; Jayasankar, J. (Journal of Buffalo Science, 2013)
Bhadawari is one of the recognized buffalo breeds of India and is famous for high fat content in their milk. Data on production and reproductive traits were collected under Network Project on Bhadawari buffaloes, at Indian Grassland and Fodder Research Institute, Jhansi, Uttar Pradesh, India. The overall least squares means (±SE) for peak yield, days to attain peak yield, lactation milk yield, lactation length, 305 days milk yield, milk yield per day of lactation, service period, calving interval and dry period were 6.96±0.10 kg, 52.8±4.1 days, 1250.5±24.6 kg, 291.4±4.9 days, 1213.5±21.6 kg, 4.30±0.06 kg, 172.4±7.7 days, 522.1±12.1 days and 241.80±11.3 days, respectively. Period of calving had a significant (p<0.05) to highly significant (p<0.01) effect on all the traits studied except service period and dry period, where it was not significant. Season of calving had a significant (p<0.05) effect or lactation length and highly significant (p<0.01) effect on lactation milk yield, 305 days milk yield and all the reproductive traits under study. The lowest calving interval, service period and dry period were observed in rainy season calvers and they differed significantly (p<0.01) with winter and summer calvers. Parity had a significant effect (p<0.05) on lactation milk yield, 305 days milk yield and milk yield per day of lactation. Pair-wise comparison revealed that lactation milk yield was highest in the 2nd lactation followed by 3rd and 4th lactation. Large coefficient of variation observed for different traits under study indicates that there is enough scope for improvement in the production and reproduction traits. Better breeding management and selection for increased performance is needed for genetic improvement of these traits.